Epidemiology of cardiac implantable electronic device infections: incidence and risk factors. (23rd June 2021) - Han, Hui-Chen; Hawkins, Nathaniel M; Pearman, Charles M; Birnie, David H; Krahn, Andrew D
Abstract: Cardiac implantable electronic device (CIED) infection is a potentially devastating complication of CIED procedures, causing significant morbidity and mortality for patients. Of all CIED complications, infection has the greatest impact on mortality, requirement for re-intervention and additional hospital treatment days. Based on large prospective studies, the infection rate at 12-months after a CIED procedure is approximately 1%. The risk of CIED infection may be related to several factors which should be considered with regards to risk minimization. These include technical factors, patient factors, and periprocedural factors. Technical factors include the number of leads and size of generator, the absolute number of interventions which have been performed for the patient, and the operative approach. Patient factors include various non-modifiable underlying comorbidities and potentially modifiable transient conditions. Procedural factors include both peri-operative and post-operative factors. The contemporary PADIT score, derived from a large cohort of CIED patients, is useful for the prediction of infection risk. In this review, we summarize the key information regarding epidemiology, incidence and risk factors for CIED infection. Graphical Abstract: